Sternal pseudoarthrosis after resternotomy treated with the Strasbourg Thoracic Osteosyntheses System: a case report - Janilionis, Ričardas; Falcoz, Pierre-Emmanuel; Jovaišas, Vytautas; Jagelavičius, Žymantas; Valančius, Ramūnas (Acta medica Lituanica, 2013)
Sternal dehiscence is a serious complication after general thoracic and cardiac surgery. Sternal resuturing, performed by simple rewiring or technical modification of rewiring, can fail overall when the bone quality is poor or the sternum is completely destroyed. A number of different sternal closure systems, consisting of plates, screws, clips and titanium bars, have been recently intoduced to treat the complicated sternal dehiscence. We describe the use of the Strasbourg Thoracic Osteosyntheses System (STRATOS) to treat complicated sternal dehiscence causing chest and back pain, sternum and chest instability, which was applied for the first time in Lithuania.
Keywords: sternotomy; sternal pseudoarthrosis; sternal osteosynthesis; chest instability; STRATOS